Pengaruh Produk Wisata terhadap Kepuasan Pengunjung Museum Sri Baduga Bandung - Dava Albamah Hafidin; Gilang Pratama Putra; Irena Novarlia (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to analyze the influence of tourism products on visitor satisfaction at the Sri Baduga Museum Bandung. The tourism products analyzed include tourist attractions, tourist facilities, amenities, and accessibility. This study uses a quantitative approach with a survey method, where data is collected through questionnaires distributed to museum visitors. Respondents were randomly selected, and the data obtained were analyzed using a simple linear regression technique to see the relationship between the independent variable (tourism product) and the bound variable (visitor satisfaction). The results of the study show that all components of tourism products, namely tourist attractions, tourist facilities, amenities, and accessibility, have a significant effect on the satisfaction of visitors to the Sri Baduga Museum Bandung. Tourist attractions were found to be the most dominant factor in influencing visitor satisfaction, followed by facilities and accessibility. In addition, the results of the analysis also showed that the majority of visitors were satisfied with their experience at the museum, and this was reflected in their desire to visit again and their willingness to recommend the museum to friends and family. Based on these findings, it can be concluded that the quality of tourism products at the Sri Baduga Museum Bandung has an important role in increasing visitor satisfaction. Recommendations are given to museum managers to continue to improve the quality of attractions, facilities, and accessibility to maintain and increase visitor satisfaction. This research is expected to be a reference for the development of more effective tourism strategies in the future.